1995
DOI: 10.1002/hlca.19950780110
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Stabilization of DNA: Oligonucleotides containing 7‐substituted 7‐deazaadenines

Abstract: The oligonucleotide building blocks 4b-d derived from 7-bromo-, 7-chloro-, and 7-methyl-substituted 7-deaza-2'-deoxyadenosines 3bd were prepared. They were employed in the solid-phase synthesis of the oligonucleotides 7-25. The dA residues of the homomer d(A12), the alternating d[(A-T),], and the palindromic d(G-T-A-G-A-A-T-T-C-T-A-C) were replaced by 3 M as well as by the parent 7-deaza-2'-deoxyadenosine (3a). The melting profiles and CD spectra of oligonucleotide duplexes, showing this major groove modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 40 publications
(28 reference statements)
1
46
2
Order By: Relevance
“…[50][51][52][53][54][55][56][57][58][59] All the substituents shown are stabilizing relative to deoxyuridine (which has hydrogen at the C-5 position), including the C-5 methyl group of thymidine (1). Structures of deoxycytidine (9) and some modified deoxycytidine nucleosides which have increased surface area by addition of extra rings (10)(11)(12).…”
Section: Figurementioning
confidence: 99%
“…[50][51][52][53][54][55][56][57][58][59] All the substituents shown are stabilizing relative to deoxyuridine (which has hydrogen at the C-5 position), including the C-5 methyl group of thymidine (1). Structures of deoxycytidine (9) and some modified deoxycytidine nucleosides which have increased surface area by addition of extra rings (10)(11)(12).…”
Section: Figurementioning
confidence: 99%
“…In this case, it was not possible to obtain a sigmoidal melting profile, probably due to counter-ion condensation of the ammonium-ion-tethered oligomer. On the other hand, the duplex 46´48 containing ethynyl residues exhibited an increased stability that was superior to that of the parent 46´47 [32].…”
Section: Methodsmentioning
confidence: 84%
“…Earlier our laboratory has shown that 7-substituents of 7-deazapurines as well as of 8-aza-7-deazapurines are well accommodated in the major groove of DNA (12)(13)(14)(15). In particular, halogen substituents show favorable properties with regard to duplex stability.…”
Section: Oligonucleotidesmentioning
confidence: 99%
“…This problem was approached by replacing the purine moiety of compound 1 by other heterocyclic bases. 7-Deazapurines (pyrrolo [2,3-d]pyrimidines) (purine numbering is used throughout Results and Discussion) and 8-aza-7-deazapurines (pyrazolo [3,4-d]pyrimidines) have already been used in the case of adenine and guanine nucleosides to alter duplex stability (12)(13)(14)(15). These heterocycles mimic the shapes of the purines and can substitute for purine bases in Watson-Crick base pairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation